Glass Ceiling and Personal Sense of Power: Challenges in Women’s Career Advancement (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2023)
Women’s involvement in the labor market continues to increase, but this does not happen to women in career leadership positions. In fact, women’s career advancement continues to experience obstacles and individual power plays a role in their career advancement efforts. The purpose of this research is to identify the challenges of improving women’s careers, their personal sense of power, and their efforts in improving their careers. The approach used was qualitative with an instrumental case study design. An open-ended questionnaire was distributed to get participants who fit the criteria to be interviewed, namely women who have worked for more than 1 year, there is a career ladder in their workplace, and participants indicated experiencing a glass ceiling. The results of research on four participants showed that the challenges that are still often faced by working women are discrimination in the work environment, family environment expectations regarding women’s domestic roles, and internalization of feminine roles in individuals. Participants indicated to have different personal sense of power, ranging from low to high. Individuals with a high personal sense of power tend to dare to express their opinions and are able to make structured plans for career development. While individuals with a low personal sense of power tend to be more silent, but still show a desire to develop a career.